1994
DOI: 10.1111/j.1432-1033.1994.tb19081.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial peptides and mitochonrial presequences affect mitochonrial coupling, respiration and protein import

Abstract: Cecropins A and P1, antibacterial peptides from insects and from pig and some related peptides released respiratory control, inhibited protein import and at higher concentrations also inhibited respiration. However, PR-39, an antibacterial peptide from pig intestine, was found to be almost inert towards mitochondria. The concentrations at which the three mitochondrial functions were effected varied for different peptides. Melittin, magainin and Cecropin-A-(1,13) -Melittin(l,l3)-NH2, a hybrid between cecropin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 35 publications
3
51
0
Order By: Relevance
“…These peptides also display antimicrobial activity (31). Likewise, Westerhoff et al (29,32) showed that magainins dissipated the membrane potential of isolated rat liver mitochondria and postulated that this would be the mechanism of antibacterial activity, because of the similar organization of membrane-linked energy coupling in bacteria and mitochondria.…”
Section: Discussionmentioning
confidence: 98%
“…These peptides also display antimicrobial activity (31). Likewise, Westerhoff et al (29,32) showed that magainins dissipated the membrane potential of isolated rat liver mitochondria and postulated that this would be the mechanism of antibacterial activity, because of the similar organization of membrane-linked energy coupling in bacteria and mitochondria.…”
Section: Discussionmentioning
confidence: 98%
“…However, the primary sequence is the determining factor, because the reverse sequence was inactive against the bacteria tested. Cecropin P1 is also capable of uncoupling oxidative phosphorylation in the mitochondria, but this activity is not correlated with its antibacterial activity [59].…”
Section: Cecropin P1 a Mammalian Homolog Of Insect Cecropinsmentioning
confidence: 98%
“…28). Additionally, it has long been known that presequence peptides destabilize mitochondrial membranes, potentially leading to uncoupling of respiration or to dissipation of the membrane potential (29)(30)(31)(32). Accumulation of presequences also was shown to impair mitochondrial precursor processing by direct inhibition of MPP activity (33).…”
mentioning
confidence: 99%